Introduction to the Theory of Transitional Economy - Galstyan, Gagik (Bulletin of Yerevan University G: Economics, 2014)
The present article is an attempt to present the methodological principles of the investigation of transitional societies and their economic systems and it aims to reveal and define the general regularities of economic transformation.
Keywords: transitional society and economy, economic system, the theory of transformation, the main methodological principles